2021
DOI: 10.1111/jfb.14893
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and phylogenetic analysis of fungal pathogens isolated from diseased fish in Xinjiang, China

Abstract: The outbreaks of fungal diseases in cultured fish have been severe in recent years, which is harmful to the healthy and sustainable development of fish farming. In this study, an investigation was conducted for significant fungal infections of 12 species of fish in four regions in Xinjiang, China, to understand the distribution of local fish fungal pathogens. Twenty‐six fungal strains with pathogenicity were isolated, and the challenge experiment showed that eight strains from Changji area had high infection r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…In this case, however, the deletion was the lowest found in the ITS sequence of durians (13 loci). A similar result was found in fungi (Zhang et al, 2021). According to Houde et al (2019), such a mutation has a significant value in phylogenetic relations or increases the resolution of evolutionary genetic relationships between the studied taxa.…”
Section: Multiple Sequence Alignmentssupporting
confidence: 79%
See 1 more Smart Citation
“…In this case, however, the deletion was the lowest found in the ITS sequence of durians (13 loci). A similar result was found in fungi (Zhang et al, 2021). According to Houde et al (2019), such a mutation has a significant value in phylogenetic relations or increases the resolution of evolutionary genetic relationships between the studied taxa.…”
Section: Multiple Sequence Alignmentssupporting
confidence: 79%
“…These study results align with Soumya & Nair (2017), stating that the ITS region is a part of ribosomal RNA with a high evolutionary rate but is universal for different taxa. Moreover, it can be utilized in phylogenetic studies, molecular ecology, detection, and identification of individual pathogens and non-pathogens (Zhang et al, 2021). According to Skuza et al (2019), the ITS region has proven to be one of the most informative regions for forming genetic relationships between species in the genus.…”
Section: Multiple Sequence Alignmentsmentioning
confidence: 99%
“…In contrast to traditional morphological identification, molecular identification is simple, rapid, and accurate [39][40][41]. In this study, we constructed a total of 30 phylogenetic trees based on two types of datasets to clarify phylogenetic relationships within the Lumbricidae family while finding suitable gene fragments for molecular identification.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the risk of fish disease has increased. Studies have shown that viruses, bacteria, fungi and parasites are the main causes of fish diseases, with bacterial diseases accounting for the highest proportion and causing the greatest losses (Garrido‐Olvera et al, 2022; Kibenge, 2019; Scholz et al, 2021; Zhang, Han, et al, 2021; Zhang, Xiong, et al, 2021). Aeromonas hydrophila is one of the pathogenic bacteria in fish, which can not only cause septicaemia in fish, but also pose a threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the development of fish probiotics has attracted the interest of many researchers, because these probiotics can not only inhibit the growth of fish pathogenic bacteria, but also without pollution to the environment. Zhang, Han, et al (2021); Zhang, Xiong, et al (2021) showed that Bacillus velezensis WLYS23 screened in the gut of hybrid snakehead has antagonism to 20 species of fish pathogens such as Aeromonas hydrophila , Aeromonas veronii , Aeromonas aquariorum , Aeromonas shigelloides and Nocardia seriolae . Streptomyces amritsarensis N1‐32 screened from soil by Li and Chen (2019) has an antagonistic effect on 10 fish pathogens such as Aeromonas hydrophila , Aeromonas veronii , Aeromonas caviae .…”
Section: Introductionmentioning
confidence: 99%